2014
DOI: 10.1186/1471-2164-15-760
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of differentially expressed genes and transcriptional regulation induced by salt stress in two contrasting cotton genotypes

Abstract: BackgroundCotton (Gossypium spp.) is one of the major fibre crops of the world. Although it is classified as salt tolerant crop, cotton growth and productivity are adversely affected by high salinity, especially at germination and seedling stages. Identification of genes and miRNAs responsible for salt tolerance in upland cotton (Gossypium hirsutum L.) would help reveal the molecular mechanisms of salt tolerance. We performed physiological experiments and transcriptome sequencing (mRNA-seq and small RNA-seq) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
163
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 176 publications
(172 citation statements)
references
References 120 publications
9
163
0
Order By: Relevance
“…However, only a few salt stress-inducible genes have been documented in cotton, such as GhNHX1 [25], GhDREB [26], GhERF2-GhERF6 [27][28][29], GhNAC1-GhNAC13 [30,31], GhMT3a [32], GhMPK2 [33], GhMKK5 [34], GhZFP1 [35], GhCIPK6 [36], GhWRKY17 [37], GhWRKY39-1 [38], and GbRLK [39]. With the success of the cotton whole-genome sequencing [40,41], and the widespread use of microarrays and next-generation sequencing, some salt-related regulatory factors and genes have been identified in cotton at genome-wide level [6,[42][43][44]. For example, some members of transcription factor families such as WRKY, NAC, MYB, and C2H2 have been reported to play an important role in salt tolerance of cotton [6,[42][43][44].…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations
“…However, only a few salt stress-inducible genes have been documented in cotton, such as GhNHX1 [25], GhDREB [26], GhERF2-GhERF6 [27][28][29], GhNAC1-GhNAC13 [30,31], GhMT3a [32], GhMPK2 [33], GhMKK5 [34], GhZFP1 [35], GhCIPK6 [36], GhWRKY17 [37], GhWRKY39-1 [38], and GbRLK [39]. With the success of the cotton whole-genome sequencing [40,41], and the widespread use of microarrays and next-generation sequencing, some salt-related regulatory factors and genes have been identified in cotton at genome-wide level [6,[42][43][44]. For example, some members of transcription factor families such as WRKY, NAC, MYB, and C2H2 have been reported to play an important role in salt tolerance of cotton [6,[42][43][44].…”
Section: Introductionmentioning
confidence: 98%
“…Generally, mechanisms underlying salinity tolerance in plants involve maintaining homeostasis (including ionic and osmotic homeostasis), detoxification, and growth regulation [9], and these mechanisms have been reported at the molecular level, cellular level, and whole plant level [10]. Previous studies identified a possible mechanism involved in the salt-stress response in cotton [6,[11][12][13][14] and Arabidopsis [15][16][17]. When exposed to salt stress, plants maintain ionic homeostasis (i.e., a low concentration of Na + and a high concentration of K + ) in the cytosol [18].…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…So far, miRNAs have been identified in a few aquatic crustacean species, and these were involved in regulation of oocyte meiosis , adaptive immunity Ou et al 2012;Zeng et al 2015), and drug response (ValenzuelaMiranda et al 2015). Previous reports have shown that some plant miRNAs respond to salinity stress and that some miRNA targets are salt stress-related genes (Xie et al 2014;Peng et al 2014;Frazier et al 2011). This suggests that miRNAs play important roles in plant salt stress responses.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%